High magnetic coercive field in Ca‐Al‐Cr substituted strontium hexaferrite - Stingaciu, Marian; Mishra, Durgamadhab; de Julián Fernández, César; Cabassi, Riccardo; Eikeland, Anna Zink; Christensen, Mogens; Deledda, Stefano (Journal of alloys and compounds, 2021)
•Ca–Al–Cr substituted strontium hexaferrite powders were synthesized by sol-gel.•The magnetoplumbite structure is preserved, even for large levels of substitutions.•High coercivity fields (up to 1.4 T) were observed at room temperature. [Display omitted] The structural and magnetic properties of Sr0.67Ca0.33Fe9Al3−xCrxO19 submicrometric powders with substitution levels ranging from x = 0 up to x = 3, prepared by sol-gel synthesis method, have been investigated. The powders were characterized by high resolution synchrotron X-ray diffraction, scanning electron microscopy, powder neutron diffraction and MPMS-SQUID magnetometer. The structural analysis shows that upon Ca-substitution of SrFe12O19 at the Sr site and Al–Cr at the Fe sites, the magnetoplumbite structure is preserved, even for large levels of substitutions. The X-ray powder diffraction peak broadening and Williamson-Hall plots analyses indicate an increase of crystallites size and relaxation of the microstrain with increasing amounts of Chromium. The magnetic hysteresis loops reveal high coercivity fields at room temperature, with the highest value of HC = 1125 kA/m (1.41 T) obtained for Sr0.67Ca0.33Fe9Al2.5Cr0.5O19 powder interesting to develop free-Rare Earth high coercivity magnets. The saturation magnetization and remanence values increase monotonically with increasing Cr content while the switching field decreases. The structural Rietveld refinement of combined X-ray/neutron diffraction data shows the affinity of Al3+ and Cr3+ cations to migrate mainly towards (2a) Fe-Oh2 and (12k) Fe-Oh3 sites and only minor amounts is found on the (4f1) Fe-Oh1 octahedral sites. The structural observations corroborate the magnetic properties, demonstrating a correlation between the structure and magnetic properties in Ca–Al–Cr substituted strontium hexaferrite. The role of the particle size to maximize the coercivity properties is discussed.